Impact of Al2O3-Cu/Water Hybrid Nanofluid and Impinging Jet on Moving Plate at High Reynolds Numbers: A Numerical Study - Ekiciler, Recep (International Conference on Applied Engineering and Natural Sciences, 2023)
Numerical research utilizing the commercial code ANSYS FLUENT is conducted to examine the heat transfer from a heated moving surface caused by confined slot-jet impingement at high Reynolds numbers. Confined slot-jet impingement's flow and thermal fields are studied using the SST k-w turbulence model. Important parameters such as high Reynolds numbers (50000, 100000, and 150000), different working fluids (water and 1.0% Al2O3-Cu/water hybrid nanofluid), and different impinging surface velocities (Vp=0, 2, and 3 m/s) are investigated on Nusselt numbers, skin friction factors, temperature contours, and velocity streamlines. According to the results, it is determined that the Nusselt number increased as the impinging surface’s velocity increased. While the Nusselt number grows with the increament in the Reynolds number, the skin friction factor tends to decrease. The utilization of 1.0% Al2O3- Cu/water hybrid nanofluid as the working fluid also has a substantial influence on heat transfer.